A study on the acceptance factors for sustainable farming technology among farmers registered with farmer organisation authority Malaysia (FOAM) - Sa’ari, Juan Rizal (2022)
Sustainable farming technology (SFT) is a farming system that is capable of maintaining farmers' productivity. It has captured the interest of developing countries and the numbers are growing as it relies on natural and human resources. However, farmers in Malaysia are still not familiar with sustainable farming. There is low awareness about SFT and the Malaysian agriculture sector has experienced a low adoption rate of SFT practices and indicates only a few farmers have accepted it. The aim of this study is to fill up the above- mentioned gaps by looking into acceptance of SFT among farmers registered with (FOAM). A quantitative methodology based on employing a structured questionnaire was used for data collection. The proposed research model and its hypothesis are tested using Partial Least Square (PLS-SEM) technique on a data set of 198 farmers registered under Farmers Organization Authority Malaysia (FOAM). Results showed that Facilitating Conditions are the most important factors in the structural relationship between exogenous and endogenous constructs. It is followed by Performance Expectancy, Effort Expectancy, Access to Finance, Government Support and Social Influence. Furthermore, the findings also indicated that Performance Expectancy, Effort Expectancy, Facilitating Condition and Access to Finance were found to have a significant influence on the acceptance of SFT among Farmers registered with (FOAM). However, Social Influence and Government Support were found non-significant influence to accept SFT among Farmers registered with (FOAM). Moreover, the findings indicate that Government Support moderates Performance Expectancy, Social Influence, Facilitating Condition and Access to Finance to accept SFT among farmers registered with (FOAM). However, only Effort Expectancy non-significantly related to being moderated by the Government Support. Theoretical, statistical techniques and managerial contribution of the study were explained as well as the implications of research to different levels, such as farmers and policy makers. The findings provide empirical evidence for the farmers to incorporate into their decision making. It will guide the farmers to accept SFT and how to further enhance its effectiveness and efficiencies. By having these results as guidance, it may be used as a comprehensive reference to guide future farmers so that they would have an improved knowledge and understanding towards SFT acceptance, and therefore, the SFT will be more efficient. The limitations of this study were discussed, as well as the recommendations for the farmers, policy makers and future researchers concerning additional variables such as mediating or moderating factors. Furthermore, future studies are also recommended to employ other types of instruments and include other statistical tests.